Unsteady flow interactions and ground plane proximity in a coupled compact intake-fan in crosswind - Lobuono, Luca; MacManus, David G.; Hueso Rebassa, Josep; Christie, Robert (Elsevier, 2026)
The assessment of the crosswind flow separation and resulting intake flow distortion can be a key consideration for the design of viable large civil aeroengines. Under crosswind conditions, the intake aerodynamics are strongly influenced by both the fan and the ground plane. However, the impact of key design parameters, such as ground clearance, on the intake flow distortion is not fully understood. This study investigates the effects of a large variation in ground clearance on the intake-fan unsteady aerodynamics using Unsteady Reynolds-Averaged Navier-Stokes (URANS) simulations of a fully coupled rotating fan stage. The work includes an assessment of the unsteady swirl distortion and the unsteady peak distortion events. The findings show that increased ground clearance can have adverse effects on the intake flow distortion. Gross separation can occur at lower crosswind velocities which arise at the intake lower quadrant due to mass flow redistribution. Conversely, the gross separation on the windward side of the intake occurs at a greater crosswind velocity for an increased ground clearance. However, this separation also exhibits greater levels of the azimuthal extent of the unsteady intake swirl distortion compared to the baseline configuration. Overall, intake designs should be assessed at the expected ground clearance as the flow distortion and the onset of separation can vary substantially.
Keywords: 40 Engineering; Mechanical Engineering & Transports; 4012 Fluid mechanics and thermal engineering